2013
DOI: 10.1088/2040-8978/15/5/055101
|View full text |Cite
|
Sign up to set email alerts
|

Design of a tunable terahertz narrowband metamaterial absorber based on an electrostatically actuated MEMS cantilever and split ring resonator array

Abstract: A dynamically tunable terahertz (THz) narrowband metamaterial absorber is presented. The absorber is based on an electrostatically actuated micro-electro-mechanical systems (MEMS) cantilever and split ring resonator (SRR) array. An equivalent LC circuit model for a transverse electric (TE) polarization wave is introduced to analyze the mechanism of frequency tuning. A finite element method is applied to simulate the mechanical characteristics of the cantilever, and a finite integration technique is used to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 27 publications
(30 reference statements)
0
35
0
Order By: Relevance
“…We combine meta-atoms that support strongly localized modes with flat, suspended silicon nitride membranes that can be driven electrostatically. Unlike tunable absorbers based on tilted cantilevers 32,41 , flat membranes can maximize the coupling between meta-atoms and the ground plane and enhance the modulation contrast by avoiding resonance broadening due to tilting. Our prototype devices show very good performance: strong absorption (60-80% at the initial state when the membranes remain suspended), fast switching speed (switching time ∼27 μs), highly enhanced mechanical sensitivity (δλ 0 /δd can be up to 14.8 when the device is driven to snap-down), and large modulation contrast (up to 65% of absolute change in absorption at the initial resonance under the snap-down state).…”
Section: Introductionmentioning
confidence: 99%
“…We combine meta-atoms that support strongly localized modes with flat, suspended silicon nitride membranes that can be driven electrostatically. Unlike tunable absorbers based on tilted cantilevers 32,41 , flat membranes can maximize the coupling between meta-atoms and the ground plane and enhance the modulation contrast by avoiding resonance broadening due to tilting. Our prototype devices show very good performance: strong absorption (60-80% at the initial state when the membranes remain suspended), fast switching speed (switching time ∼27 μs), highly enhanced mechanical sensitivity (δλ 0 /δd can be up to 14.8 when the device is driven to snap-down), and large modulation contrast (up to 65% of absolute change in absorption at the initial resonance under the snap-down state).…”
Section: Introductionmentioning
confidence: 99%
“…To date there have been several demonstrations of MEMS techniques utilized to achieve tunable response at THz and lower frequencies and near infrared wavelengths as well as for constructing diffractive gratings . In our study, the metamaterial unit cell (shown in Figure ) consists of four layers above a carrier substrate.…”
mentioning
confidence: 99%
“…One possible way to achieve frequency tunability of MA is to reconstruct the geometries, but it cannot be applied in the case of dynamic tuning. A tunable MA based on electrostatically actuated MEMS cantilever 11 or varactor loaded resonator 12 has been proposed. However, the fabrication of such structures is complicated.…”
Section: Introductionmentioning
confidence: 99%